Analysis of the disease burden of benign prostatic hyperplasia in China, the United States and Germany at 1990 and 2019 - LU Peiwen; ZI Hao; QIAN Xinhang; MING Daojing; FANG Cheng; LI Xiaodong (Yixue xinzhi zazhi)
Objective To comparatively analyze the disease burden of benign prostatic hyperplasia (BPH) in China, the United States, and Germany between 1990 and 2019. Methods The Global Burden of Disease 2019 (GBD 2019) was used to comparatively study the prevalence, incidence, years lived with disability (YLD), and standardized rate in China, the United States and Germany between 1990 and 2019. Results Compared with 1990, the number of prevalence cases, incidence cases and YLD in China, the United States and Germany all showed an increasing trend in 2019. The prevalence, incidence and YLD rate of BPH patients of all ages in China continued to increase with age, with the highest BPH incidence occuring in the age group of 75~79 years old. In 2019, the prevalence of BPH and YLD rate in the United States increased with age, and were the highest among the elderly aged 80 and above, while the incidence of BPH was the highest in the age group of 70~74 years old. In 1990 and 2019, the incidence of BPH among people aged from 65 to 69 in Germany was the highest, and the age group with the highest prevalence was 75 to 79 years old. BHP patients in 75-79 age group has the highest YLD in Germany. From 1990 to 2019, YLD showed an increasing trend in all three countries. In 2019, the YLD of BPH in China, the United States and Germany was 406,200, 89,400 and 27,300 person-years respectively. Conclusion China, the United States, and Germany bear a heavy disease burden of BPH, with China having a higher BPH disease burden than the United States and Germany, particularly among those over 65 years of age and populations in rural and remote areas. Proactive health guidance should be provided for highrisk groups in the future, along with a greater allocation of medical resources.